The effectiveness of online Mathematics learning - Akhsanul In'am; Siti Hajar (AMCA Journal of Community Development, 2021)
This study aims to analyze the effectiveness of online Mathematics learning. It employed qualitative research design with case-study technique. Subjects of this study were 7th graders from five different classes at Madrasah Tsanawiyah Negeri 1 Malang. Data collection methods were observations, documents of zoom learning, and interviews with student guardians. The obtained data were analyzed through data description. Results showed that there were disturbances in the online learning activities. Among the problems were student punctuality and unstable internet connection activities. During the online learning, most students could not follow the lesson very well, and only few responded to the teachers. There were also problems in students’ monitoring and evaluation. These aspects of learning activities, students’ responses, and monitoring and evaluation implied that online Mathematics learning was ineffective.